Understanding How Baby Boomers Use the Internet and Social Media to Improve the Engagement with Brands - Carrillo-Durán,María-Victoria (2022)
Abstract: The emergence of the baby boomers, as a new group of people aged 55 to 75, with unique interests, media exposure and shopping habits, set a before and after in the language that brands must speak. The main objective of social media is to build engagement, and in the digital environment, it means engaging both seniors and companies. For this, learning how they act in the digital environment is key. This paper aims to show how baby boomers behave in this environment, showing the challenges and advantages brands have to reach them effectively. Based on an exploratory and qualitative study with focus groups of senior internet and social network users from Portugal and Spain, the results show that analysing their habits of exposure to these media and the interests, brands do not seem to speak the same language they do, and that is why baby boomers do not feel engaged with them online. This work provides recommendations to get this engagement and improve the digital experience. In this line, to build this engagement, brands need to understand the variables of interest for baby boomers stemming from this study: affiliation and support. On the other hand, they must assume that this level of engagement will depend on establishing an active dialogue, with content targeted at different segments of the population, related to the variables above (affiliation and support), and to a degree enough to reach baby boomers emotionally.